(untitled) (Eurasian Research Bulletin, 2021)
The science of semiotics, which originated in French linguistics and developed in world linguistics, is becoming the most comprehensive and important object of modern comparative linguistics. It evolves from linguodidactic, linguocultural areas to neuropsycholinguistic areas. Communicative communication helps to create the most convenient ways to establish communication. In particular, steps are being taken towards linguodidactic semiotics in teaching foreign languages. The article briefly describes the theoretical issues of semantics and scientific observations of its development